2000
DOI: 10.1126/science.288.5468.1051
|View full text |Cite
|
Sign up to set email alerts
|

Influenza B Virus in Seals

Abstract: Influenza B virus is a human pathogen whose origin and possible reservoir in nature are not known. An influenza B virus was isolated from a naturally infected harbor seal (Phoca vitulina) and was found to be infectious to seal kidney cells in vitro. Sequence analyses and serology indicated that influenza virus B/Seal/Netherlands/1/99 is closely related to strains that circulated in humans 4 to 5 years earlier. Retrospective analyses of sera collected from 971 seals showed a prevalence of antibodies to influenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
244
0
11

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(259 citation statements)
references
References 17 publications
4
244
0
11
Order By: Relevance
“…The Beijing strain circulated in 1999 (WHO, 1999) (640) were found against the Sichuan strain in 5% of the seals studied (Table 1), but the HAI titers of some sera against antigens of the other strains were also high (320 against Beijing in 5% of the samples and 160 against Hong Kong in 16% of the samples studied). The results were consistent with those proposed by Osterhaus et al (2000) and Ohishi et al (2002), which suggested that influenza B virus was not restricted to humans.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The Beijing strain circulated in 1999 (WHO, 1999) (640) were found against the Sichuan strain in 5% of the seals studied (Table 1), but the HAI titers of some sera against antigens of the other strains were also high (320 against Beijing in 5% of the samples and 160 against Hong Kong in 16% of the samples studied). The results were consistent with those proposed by Osterhaus et al (2000) and Ohishi et al (2002), which suggested that influenza B virus was not restricted to humans.…”
supporting
confidence: 92%
“…It was believed that influenza B virus only infects humans, but in 2000 an influenza B virus isolate from an infected harbor seal (Phoca vitulina) was reported (Osterhaus et al, 2000).…”
mentioning
confidence: 99%
“…Influenza A viruses infect humans and other mammals and birds, whereas influenza B viruses exclusively infect humans with an exception of infections of seals [12]. All of the influenza A virus hemagglutinin (HA) subtypes H1-H15 [16] and possibly H16 [4] are circulating in aquatic birds, especially in migratory ducks in nature.…”
mentioning
confidence: 99%
“…Influenza B viruses isolated from seals and pigs were likely acquired by reverse zoonotic events (Bodewes et al, 2013;Ohishi et al, 2002;Osterhaus et al, 2000;Ran et al, 2015). Although several studies have described infection of ferrets with influenza type B viruses (Huang et al, 2014;Kim et al, 2009), we were interested in understanding at the cellular level how appropriate the ferret model is for the study of human influenza B viruses.…”
Section: Introductionmentioning
confidence: 99%